Analysis of the Effect of Artificial Aging on the Mechanical Properties of Al 2014 - Riski, Riski; Abu, Risal; Mukhnizar, Mukhnizar (The Future of Education Journal, 2025)
Aluminum alloy 2014 (Al 2014) is an Al-Cu–based alloy widely used in the aerospace and automotive industries due to its high mechanical strength. However, the mechanical properties of this alloy are strongly influenced by heat treatment, particularly the artificial aging process. This study aims to analyze the effect of artificial aging on the mechanical properties of Al 2014, especially hardness. The Al 2014 samples underwent solution heat treatment at a specified temperature, followed by rapid cooling (quenching) and subsequent artificial aging at various temperatures and holding times. The mechanical test results show that increasing the aging temperature and duration significantly affects the formation of strengthening precipitates, leading to increased hardness until reaching the optimum condition (peak aging). However, excessive aging results in overaging, which reduces mechanical properties due to coarsening of precipitates. Therefore, a precise artificial aging process is essential to optimize the mechanical performance of Al 2014 for engineering applications.